2009
DOI: 10.5194/angeo-27-1321-2009
|View full text |Cite
|
Sign up to set email alerts
|

Pre-storm <I>Nm</I>F2 enhancements at middle latitudes: delusion or reality?

Abstract: Abstract.A critical analysis of recent publications devoted to the NmF2 pre-storm enhancements is performed. There are no convincing arguments that the observed cases of NmF2 enhancements at middle and sub-auroral latitudes bear a relation to the following magnetic storms. In all cases considered the NmF2 pre-storm enhancements were due to previous geomagnetic storms, moderate auroral activity or they presented the class of positive quiet time events (Qdisturbances). Therefore, it is possible to conclude that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…19-23, 2001 andMay 13-17, 2005 storms is observed to be largely control by large southward magnetic field component, high plasma temperature, increase in proton density, flow speed stream and high plasma beta, and these period has no definite effect on the ionospheric foF2, which support the previous study of Chukwuma (2010), Makhailov andPerrone (2009), Liu et al (2008), Lastovicka (2007, 2008), Balasis et al (2006) but may result in large ionospheric effect at the main phase period.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…19-23, 2001 andMay 13-17, 2005 storms is observed to be largely control by large southward magnetic field component, high plasma temperature, increase in proton density, flow speed stream and high plasma beta, and these period has no definite effect on the ionospheric foF2, which support the previous study of Chukwuma (2010), Makhailov andPerrone (2009), Liu et al (2008), Lastovicka (2007, 2008), Balasis et al (2006) but may result in large ionospheric effect at the main phase period.…”
Section: Discussionsupporting
confidence: 87%
“…The pre storm effect on ionospheric F2 layer has been thought very puzzling, of which Makhailov and Perrone (2009) has shown that there is no such effect as the prestorm electron concentration of ionospheric F2 enhancement as a phenomenon inalienably related to the following magnetic storm. The observed nighttime electron concentration of ionospheric F2 enhancements at subauroral latitudes may result from plasma transfer from the plasma ring area by meridional thermospheric wind.…”
Section: Introductionmentioning
confidence: 97%
“…Under the average TAD velocity at F2-region heights of 500-600 m s −1 (Bruinsma and Forbes, 2010;Mikhailov and Perrone, 2009;Mikhailov et al, 2012), the arrival of a TAD at middle latitudes is expected in 2-3 h.…”
Section: Discussionmentioning
confidence: 99%
“…The first and the second common high-energy regions are marked by white rectangles, corresponding to the long time effect for the periods 12-18 April 2008 and 20-26 April 2008, respectively. The reason is that the ionosphere can be enhanced or decreased during the geomagnetic activity period for several days before and after a geomagnetic storm (Liu et al, 2008a, b;Zhao et al, 2009;Mikhailov and Perrone, 2009). In addition, many high-energy regions containing short time effects (marked by red ellipses) also emerged, corresponding to the dates 29 and 30 April and 1 and 6 May 2008, respectively.…”
Section: Wenchuan Earthquakementioning
confidence: 99%